Like mother, like daughter eaudiobook - McCreight, Kimberly (Books on Tape, 2024)
NATIONAL BESTSELLER! • From the New York Times bestselling author of Reconstructing Amelia: A daughter races to uncover her mother's secret life in the wake of her disappearance • "A breathless, shocking thriller." —Jodi Picoult The past never stays buried for too long, and what you don't know can definitely hurt you.⁠ “Deeply satisfying”—Angie Kim • “Gripping and bingeable."—Ana Reyes • “As suspenseful as it is thought-provoking."—Greer Hendricks When Cleo, a student at NYU, arrives late for dinner at her childhood home in Brooklyn, she finds food burning in the oven and no sign of her mother, Kat. Then Cleo discovers her mom’s bloody shoe under the sofa. Something terrible has happened. But what? The polar opposite of Cleo, whose “out of control” emotions and “unsafe” behavior have created a seemingly unbridgeable rift between mother and daughter, Kat is the essence of Park Slope perfection: a happily married, successful corporate lawyer. Or so Cleo thinks. Kat has been lying. She’s not just a lawyer; she’s her firm’s fixer. She’s damn good at it, too. Growing up in a dangerous group home taught her how to think fast, stay calm under pressure, and recognize a real threat when she sees one. And in the days leading up her disappearance, Kat has become aware of multiple threats: demands for money from her unfaithful soon-to-be ex-husband; evidence that Cleo has slipped back into a relationship that’s far riskier than she understands; and menacing anonymous messages from her past—all of which she’s kept hidden from Cleo . . .  Like Mother, Like Daughter is a thrilling novel of emotional suspense that questions the damaging fictions we cling to and the hard truths we avoid. Above all, it’s a love story between a mother and a daughter, each determined to save the other before it’s too late.